2021
DOI: 10.35440/hutfd.898077
|View full text |Cite
|
Sign up to set email alerts
|

Altered Autonomic Functions in Exam Stress: Cardiovascular-Pulmonary Interactions

Abstract: Background:Medical training involves a long and exhaustive curriculum in which students are frequently evaluated by examinations. Pre-examination stress is a common condition faced by students prior to exams and is one of the most widely experienced problems for medical students. The aim of the study was to assess the effects of exam stress on autonomic nervous system functions of students through cardiovascular parameters and respiratory tests. Materials and Methods:The study group consisted of 29 second-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For example, excess BP reactivity is associated with altered α- and β-adrenoreceptor sensitivity, endothelial dysfunction, increased vascular resistance, and vascular remodeling. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…For example, excess BP reactivity is associated with altered α- and β-adrenoreceptor sensitivity, endothelial dysfunction, increased vascular resistance, and vascular remodeling. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that examination-related stress increases SBP and DBP and lowers BRS values during the exam period compared to the semester time in healthy college students. 10 12 An examination can lead to significant stress, which can put the cardiovascular system at risk even in young, healthy individuals. The stress levels are even higher for medical students during their pre-examination period.…”
Section: Discussionmentioning
confidence: 99%
“…The stress levels are even higher for medical students during their pre-examination period. Constant exposure to stress is harmful in the long run as it disrupts the homeostatic balance and may be a risk factor for derangements in the cardiovascular and respiratory systems, 12 leading to disease. In a study conducted on medical students using academic examinations as a model of mental stress, it was found that the mean arterial pressure increased and the mean RR interval, SDNN, and pNN50 were significantly reduced during examinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation